Social contexts of early education, and reconceptualizing play (II) - Reifel, Robert Stuart; Brown, Mac H. (Elsevier JAI, 2004)
This volume revisits a number of themes that have appeared in earlier "Advances" publications, including "Social Contexts of Early Development" and "Education and Reconceptualizing Play". New social contexts for early education and care often require that we aim our inquiry at social conditions that have not existed in the past, as well as elaborating long-standing concerns. Studies of some of the social contexts of early education point to how many of the needs of the field are unique, depending on where and when we do our work, and with whom we work. "Reconceptualizing Play" points to the multiple perspectives that teachers, researchers, parents, and children bring to our understanding of play. Culture, policy, belief, and values prove to be worthy lenses for enhancing our developmental views of childhood play and practice. Our hope is that others will build on some of these reconceptualizations, to assist teachers and families to improve the lives of children in their programs.
Keywords: Early childhood education.; Child care.; Play.; Pre-school & kindergarten.; Child & developmental psychology.; Education -- Preschool & Kindergarten.; Family & Relationships -- Parenting -- Child Rearing.; elektronické knihy; electronic books